Trace-metal distribution and ecological risk assessment in sediments of a sheltered coastal area (Gulf of Gaeta, central-eastern Tyrrhenian Sea, Italy) in relation to hydrodynamic conditions - BONAMANO, SIMONE; PIAZZOLLA, DANIELE; SCANU, SERGIO; PIERMATTEI, VIVIANA; MARCELLI, MARCO (Mediterranean Marine Science, 2021)
This study investigates the relationship between sediment contamination and hydrodynamic conditions in the Gaeta Gulf (Tyrrhenian Sea, Italy), an anthropogenically impacted and sheltered coastal area. The pollution levels, potential toxicity, and ecological risk of trace metals were analysed in 16 sediment sampling sites using Sediment Quality Guidelines (SQGs), the Adverse Effect Index (AEI), and the Mean ERM Quotient (m-ERM-Q). The bottom shear stress of the study area, evaluated using an annual simulation of a 3D numerical model, was used to calculate a new Sediment Mobilisation Index (SMI) that detects the coastal zones where a low probability of sediment resuspension occurs. As, Ni, and Cu concentrations exceeded the Threshold Effects Level (TEL) guideline value and AEI limit in several sampling sites, indicating their ability to produce adverse effects on biota. Moreover m-ERM-Q showed the highest values of potential ecological risk in most of the sampling sites located in the inner part of the Gulf of Gaeta. In this area, the highest SMI values were also identified, demonstrating that there is a tight relationship between the two indexes (R2 = 0.8214). The application of SMI in sheltered areas will help achieve high performance of monitoring and hazard assessment tools through obtaining predictable responses on hotspot identification.